ANALISIS FAKTOR−FAKTOR YANG MEMPENGARUHI PRODUKSI KOPI MASYARAKAT DI KEC. DAMPIT, KAB. MALANG - Inosensius Harmin Jandu; Nur Ida Iriani; Dyanasari Dyanasari (Universitas Tribhuwana Tunggadewi, 2019)
Plantation sub-sector is part of the agricultural sector which acts as one of the country's foreign exchange-earners, producer of consumption materials, producers of raw materials for industry, employment providers and encourages agribusiness and supports environmental conservation. The role of plantations is increasing along with the creation of resilient agriculture by utilizing natural resources optimally supported by quality human resources. In this study, the analytical method used is multiple regression analysis models with the help of the SPSS program (for Windows version 25.0). The results showed that the Land Area X1 variable was at a significance level of 95% (α = 0.05). Then it means (0.033 0.005) which means that H0 is rejected and Ha is received by the land area and has a significant positive effect on coffee production in Dampit Subdistrict, Labor an X2 significance level of 95% (α = 0.05. Then 0.246 0.05, which means H0 is received and Ha is rejected, then labor has a positive but not significant effect on coffee production in Dampit Sub-district. Superior seedlings at X3 are 95% significance level (α = 0.05. Then 0,000 0.05, which means H0 is rejected and Ha is accepted, so superior seedlings have a significant positive effect on coffee production in Dampit District, Fertilizer X4 at a significance level of 95% (α = 0.05. then 0.005 0.05 which means H0 is rejected and Ha is accepted) Fertilizers have a significant positive effect on coffee production in Dampit District. Pesticides at X5 at a significance level of 95 % (α = 0.05. So that means (0.927 0.05) which means that H0 is accepted and Ha is rejected then pesticides have a positive but not significant effect on coffee production in Dampit District.